2021
DOI: 10.1071/sh21015
|View full text |Cite
|
Sign up to set email alerts
|

Internal and external sexual consent during events that involved alcohol, cannabis, or both

Abstract: Background Substance-involved sexual activity is common. Even though people recognise that substance-related impairment can be a barrier to people’s ability to consent to sexual activity, most do not believe that substance use automatically negates sexual consent. We extended previous work on substance-related effects on internal and external consent by investigating sexual events that involved alcohol, cannabis, or both. Methods: For 28 days, 113 participants (MAge = 29.2 years, 57.5% women, 70.8% White) resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…As such, perhaps some people's capacity for sexual decision making persists even past .08. Although research suggests that people who are intoxicated tend to have diminished internal consent feelings (Jozkowski & Wiersma, 2015;Willis et al, 2021), participants in our study may not believe this level of intoxication infringed on their ability to consent. And in some instances, for some people, it may not.…”
Section: Np145mentioning
confidence: 66%
“…As such, perhaps some people's capacity for sexual decision making persists even past .08. Although research suggests that people who are intoxicated tend to have diminished internal consent feelings (Jozkowski & Wiersma, 2015;Willis et al, 2021), participants in our study may not believe this level of intoxication infringed on their ability to consent. And in some instances, for some people, it may not.…”
Section: Np145mentioning
confidence: 66%
“…However, substance use remains a notable risk factor for nonconsensual sexual activity given that alcohol is involved in about half of sexual assaults ( Abbey et al, 2001 ) and men are more likely to use alcohol or drugs to facilitate sexual assault than other strategies ( Gidycz et al, 2011 ). Further, recently published data suggested that level of impairment should be emphasized when considering consent to substance-involved sexual activity; of note, participants in that study reported diminished levels of internal consent feelings during sexual events that involved either greater alcohol consumption or the combined use of alcohol and cannabis ( Willis et al., 2021b ). Future work on how people differentiate consensual versus nonconsensual substance-involved sexual activity is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous research, we drafted an initial list of 30 sexual behaviors that people engage in (see Appendix). Most behaviors and contexts were adapted from Herbenick et al’s (2017) study on sexual diversity; we added substance-involved sexual behaviors due to the importance of considering alcohol and drugs when assessing sexual consent (e.g., Willis et al, 2021b ). We conducted a pilot study that asked participants which of these behaviors they had engaged in.…”
Section: Methodsmentioning
confidence: 99%
“…Prior work with alcohol and sexual consent has focused on how people perceive alcohol-intensive environments or the consumption of alcohol as signs of consent (Jozkowski et al, 2017(Jozkowski et al, , 2018King et al, 2020); researchers have also explored how people's acute intoxication levels related to their hypothetical perceived ability to consent (Drouin et al, 2019). Yet, researchers rarely examine how people's drinking behaviors relate with their perceptions of sexual activity as consensual or consent communication, even though the pharmacological effects of alcohol may alter how people communicate sexual consent-effects that may become more pronounced the more alcohol someone consumes (Willis, Marcantonio, & Jozkowski, 2021).…”
Section: Typical and Binge Drinkingmentioning
confidence: 99%